2016
DOI: 10.1097/tp.0000000000001137
|View full text |Cite
|
Sign up to set email alerts
|

Nox2 and Cyclosporine-Induced Renal Hypoxia

Abstract: Background We hypothesized that Nox2 plays an important role in cyclosporine A (CsA)-induced chronic hypoxia. Methods We tested this hypothesis in Fisher 344 rats, C57BL/6J wild type and Nox2−/− mice, and in liver transplant recipients with chronic CsA nephrotoxicity. We used noninvasive molecular imaging (BOLD and DCE MRI) and molecular diagnostic tools to assess intrarenal oxygenation and perfusion, and the molecular phenotype of CsA nephrotoxicity. Results We observed that chemical and genetic inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…However, because the contralateral kidney remains intact in the UUO model, renal function is not affected [ 57 ]. Therefore, whether PEG-FUD improves renal function will necessitate future testing in a kidney disease model that affects both kidneys, such as the ischemia reperfusion injury, subtotal 5/6 nephrectomy [ 57 , 58 ], or chronic allograft nephropathy [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, because the contralateral kidney remains intact in the UUO model, renal function is not affected [ 57 ]. Therefore, whether PEG-FUD improves renal function will necessitate future testing in a kidney disease model that affects both kidneys, such as the ischemia reperfusion injury, subtotal 5/6 nephrectomy [ 57 , 58 ], or chronic allograft nephropathy [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia conceivably plays a pivotal role in CsA nephropathy. Altered microcirculation and medullary hypoxia develop as evidenced with by unenhanced MRI techniques and regional HIF expression, as well as with pimonidazole (PIM) immunostaining . Enhanced sympathetic activity and release of thromboxane, coupled with altered prostacyclin and nitric oxide production, have all been implicated as potential causes of CsA‐induced renal vasoconstriction, hypoxia and impaired GFR .…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced sympathetic activity and release of thromboxane, coupled with altered prostacyclin and nitric oxide production, have all been implicated as potential causes of CsA‐induced renal vasoconstriction, hypoxia and impaired GFR . Likewise, free radical formation by NADPH oxidase also impairs microcirculation, promoting hypoxia . The renin‐angiotensin‐aldosterone axis also plays a role in the generation of interstitial fibrosis, likely with the induction of hypoxia .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been reported that NADPH oxidase 4 (NOX4) is the NOX isoform with the highest expression in the kidney, while NOX1 and NOX2 are expressed at a lower levels and play an important role in CsA-induced oxidative stress(Rajaram et al 2019). Indeed, renal NOX4 and NOX2 mRNA/protein expressions were upregulated in CsA-rodents(Djamali et al 2016;Tan et al 2020, Bekpınar et al 2019Kalaycı et al 2023). In our study, renal NOX4 and NOX2 expressions were also upregulated in CsA-rats, and these expressions decreased due to CDCA, but did not return to normal levels.Moreover, in our study, renal NF-κB, TNF-α and IL-6 levels, and MPO activity were detected to elevate in CsA rodents as previously reported (El-Kashef et al 2018;Harb et al 2021; Nouri et al 2022), but CDCA treatment decreased TNF-α level but not MPO activity.…”
mentioning
confidence: 96%